Tantangan Digitalisasi UMKM di Kota Banjarbaru dan Implikasinya terhadap Keberlanjutan Usaha - Reny Marliadi; Novian Adhipurna; Ibrahim Rully Effendy; Nila Cahya; Muhammad Meftah Mafazy (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Digitalization has become an important factor in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) by improving operational efficiency, financial resilience, and competitiveness. However, many MSMEs still face challenges in adopting digital technologies effectively. This study aims to identify the digitalization challenges encountered by MSMEs in Banjarbaru City and analyze their implications for business sustainability. The study employed a descriptive exploratory quantitative approach using primary data collected through structured questionnaires administered to 62 MSME owners. The findings indicate that digitalization challenges exist in three main business aspects. In the production aspect, the major constraints include limited raw material availability, suboptimal production capacity, and the absence of systematic waste recording. In the financial aspect, although bookkeeping is carried out regularly, financial records are still predominantly maintained manually, limiting financial transparency and access to external financing. In the marketing aspect, social media has been utilized as a promotional tool; however, digital marketing practices remain basic and are not yet supported by strategic planning or data-driven analysis. These conditions have the potential to increase operational costs, reduce financial resilience, and limit market expansion opportunities. Therefore, integrated digitalization across production, financial management, and marketing is essential to strengthen MSME sustainability while providing valuable input for governments and supporting institutions in designing more targeted digitalization programs.